5-Amino-2-chloro-4-fluoro-N-(N-isopropyl-N-methylsulfamoyl) benzamide, C11H15O3ClFN3S - Jie Wang; Xiao Shu-Zhen; Cong Huang; Liu Ya-Qiang; Peng Da-Yong (Zeitschrift für Kristallographie - New Crystal Structures)
C11H15O3ClFN3S, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 7.8107(11) Å, b = 9.1644(13) Å, c = 11.3521(15) Å, α = 67.543(2)°, β = 72.776(2)∘ $72.776{(2)}^{° }$ , γ = 88.529(2)∘ $88.529{(2)}^{° }$ , V = 713.76(17) Å3, Z = 2, Rgt ${R}_{gt}$ (F) = 0.0385, wRref $wR_{ref}$ (F 2) = 0.1338, T = 296(2) K.